Oral N - Acetyl Cysteine for Meconium Ileus of Preterm Infants - Gulsum Kadioglu Simsek; Sema Arayici; Mehmet Buyuktiryaki; Nilufer Okur; Gozde Kanmaz Kutman; Serife Suna Oguz (Gynecology Obstetrics & Reproductive Medicine, 2019)
Objective: Meconium ileus of preterm infant is a kind of intestinal obstruction. There is no standard medical treatment of meconium ileus of preterm infant.